Electrocoagulation: An Overview of the Technology for Livestock Farm Wastewater Treatment - Mosammat Mustari Khanaum; Md. Saidul Borhan (Waste Technology, 2023)
Livestock operations generate wastewater which is characterized by high biological oxygen demand and chemical oxygen demand concentrations, high levels of solids including fats, oils, and grease. Its high nutrient content, particularly phosphorus and nitrogen, is an important factor because of its environmental impact. To reduce these, nutrient contaminants can either be captured or removed from liquid manure before disposal. Several techniques, including chemical, electrochemical, biological, and advanced oxidation, are used to treat this wastewater. Most of them have some limitations. Conventional and biological processes are time-consuming and cost-intensive, requiring a large treatment area, and generating large amounts of sludge. Lately, electrolysis has attracted attention as a potential strategy for wastewater treatment due to its environmental compatibility. Livestock waste chemistry differs considerably from industrial wastewater. Hence, the selection of electrode material with anode and cathode combination mode is critical to removing pollutants at low energy consumption. A total of 72 published articles were reviewed in this paper focusing on system configuration, contaminant removal, operation timing, and achievement of this electrocoagulation process. The commonly used electrode materials are aluminium, iron, and mild steel. In treating livestock wastewater, different combinations (Al-Al, Al-Fe, and Fe-Fe) and wiring modes of anode and cathode have been reported in the literature.